O primeiro Oswald de Andrade e a crítica: balbuciamento imbecil, suicídio literário e a dicotomia autenticidade / inautenticidade como critérios de brasilidade (1924-1927) - Cruvinel, Zandélli Lira (2022)
After the Modern Art Week of 1922, the modernist movement began to focus not only on what they wanted to break, but also on what they wanted to build. From the reason for the existence of the movement itself (the liberation, in the creative spirit of the artist, from the bonds and impositions of formulas and metrics), to the demand for authentic and free expression, to the questioning about the nature and character of Brazilian cultural identity, the journey The modernist movement was crossed by bigger issues than the construction of a new art. In this environment, Oswald de Andrade launched his aesthetic project Pau-Brasil (1924; 1925). In addition to Oswald's own ideas, the reception of the Pau-Brasil project can give us access to the discussion on art, nationalism, Brazilian culture and national history made between intellectuals and artists in the final years of the First Republic. Using as a conceptual instrument the proposals of Robert Jauss (1996), within the Aesthetics of Reception, and, secondarily, of Wolfgang Iser, on the Aesthetic Effect, I approach the reception, between 1924 and 1927, of the Pau-Brasil project. In terms of authentic or inauthentic, original or copy, it is the dispute over Brazilian cultural identity that fragments the modernist movement, serves as an evaluative criterion for art and denounces the fragility of a national pact in the period. Among the criticisms of Pau-Brasil, I highlight those by Graça Aranha, Tristão de Athayde and the Verdeamarelistas (Menotti Del Picchia, Cassiano Ricardo, Plínio Salgado). This group of authors verbalizes central points of criticism of the pau-brasil project: the return or the return to the irrational and the authenticity/inauthenticity dichotomy (in terms of national versus foreign).